PROSES KREATIF PENCIPTAAN TARI MULI LIMBAN WAYA - Ernanda, Fahmi (Jurnal Seni dan Pembelajaran, 2023)
This research aims to describe the creative process of creating the Muli Limban Waya dance. This research uses the concept of choreography by Y. Sumandiyo Hadi, the process of creating dance or choreography through three stages, namely exploration, improvisation and composition. The research was conducted using a qualitative descriptive method, with data collection techniques in the form of interviews, observation and documentation. The data sources in this research are primary data sources, namely dance arrangers, music arrangers and dancers, secondary data sources are documentation related to the creation process and the elements that form it. Data validity was carried out using technical triangulation. The data analysis stages involved include data reduction, data presentation, and drawing conclusions. The results of this research show that the process of creating dance goes through three stages, the first stage is exploration, producing ideas or concepts of flowing keywords which are used as movement concepts and making the Sigeh Penguten and Bedayo Tulang Bawang dances as references so as not to stray from the existing traditional dance path. The improvisation stage was carried out by developing many movements from the various Sigeh Penguten movements. The composition stage is carried out by dividing it into three plots, namely the beginning, middle and end. Family environmental factors are the main factors in the creative process of dance artists. Keywords: content, formatting, article.